2016
DOI: 10.1037/bul0000057
|View full text |Cite|
|
Sign up to set email alerts
|

A qualitative meta-analysis examining clients’ experiences of psychotherapy: A new agenda.

Abstract: This article argues that psychotherapy practitioners and researchers should be informed by the substantive body of qualitative evidence that has been gathered to represent clients' own experiences of therapy. The current meta-analysis examined qualitative research studies analyzing clients' experiences within adult individual psychotherapy that appeared in English-language journals. This omnibus review integrates research from across psychotherapy approaches and qualitative methods, focusing on the cross-cutti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
210
1
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(248 citation statements)
references
References 152 publications
17
210
1
20
Order By: Relevance
“…Systematic reviews have recently been supplemented by qualitative meta‐analyses (Timulak, ), a method that has evolved in other disciplines such as nursing but is relatively new to psychotherapy research (e.g., Timulak, ; Timulak et al., ; Timulak & McElvaney, ). Most recently, Levitt, Pomerville, and Surace () performed a comprehensive qualitative meta‐analysis of clients’ experiences of psychotherapy based on findings from 109 qualitative studies on individual therapy (1,414 clients).…”
Section: Qualitative Meta‐analyses Of Clients’ Experiences In Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews have recently been supplemented by qualitative meta‐analyses (Timulak, ), a method that has evolved in other disciplines such as nursing but is relatively new to psychotherapy research (e.g., Timulak, ; Timulak et al., ; Timulak & McElvaney, ). Most recently, Levitt, Pomerville, and Surace () performed a comprehensive qualitative meta‐analysis of clients’ experiences of psychotherapy based on findings from 109 qualitative studies on individual therapy (1,414 clients).…”
Section: Qualitative Meta‐analyses Of Clients’ Experiences In Therapymentioning
confidence: 99%
“…Levitt et al. () structured their findings around five clusters of client perceptions: (a) therapy as a process of change through structured curiosity and pattern identification; (b) the caring relationship that allows clients to benefit from therapy; (c) the therapist's professional credentials as a building block of trust as well as a source of client doubt regarding therapist authenticity; (d) the importance of collaboration and recognition of differences in the relationship; and (e) the importance of the client's agency and the need to accommodate therapy to fit the client's needs.…”
Section: Qualitative Meta‐analyses Of Clients’ Experiences In Therapymentioning
confidence: 99%
“…In another, more recent review of the significant events research, Levitt and colleagues () summarized findings from over 100 qualitative studies. They concluded that there may be one core category that best summarizes clients’ experiences in psychotherapy: “Being known and cared for supports clients’ ability to agentically recognize obstructive experiential patterns and address unmet vulnerable needs” (p. 821).…”
Section: Introductionmentioning
confidence: 99%
“…The client's experience of loss of agency in his/her life has been conceptualized as a prime reason for seeking help from conversational therapy (Wahlström, 2006) and the participation of the client as an active agent is seen as prerequisite for the change process (Levitt, Pomerville, & Surace, 2016).…”
Section: Introductionmentioning
confidence: 99%